Soccer in Munster : A Social History, 1877-1937 - Toms, David (Book collections on Project MUSE., 2015)
This book charts soccer's development in Munster from its earliest days as a game played by an elite few to a game of the everyman. Along the way, it explores the ups and downs of the sport as it was played amid war, revolution and class conflict. David Toms guides us through soccer's journey in Munster from a field in Mallow in the 1870s to the glamor and excitement of cup finals in front of crowds of thousands by the end of the 1930s. Along the way we encounter the emergence of modern sporting culture where sport is as much entertainment as exercise.